Plant Growth-Promoting Rhizobacteria Eliminate the Effect of Drought Stress in Plants: A Review - Ahmad, Hafiz Muhammad; Fiaz, Sajid; Hafeez, Sumaira; Zahra, Sadaf; Shah, Adnan Noor; Gul, Bushra; Aziz, Omar; Mahmood-Ur-Rahman,; Fakhar, Ali; Rafique, Mazhar; Chen, Yinglong; Yang, Seung Hwan; et al. (Frontiers in Plant Science, 2022)
Plants evolve diverse mechanisms to eliminate the drastic effect of biotic and abiotic stresses. Drought is the most important factor that causes huge loss to crop yields throughout the world. Osmotic stress decreases relative water contents, chlorophyll contents and increases accumulation of osmolytes, epicuticular wax contents, antioxidant enzymatic activities, reactive oxygen species, secondary metabolites, membrane lipid peroxidation and abscisic acid. Plant growth promoting rhizobacteria (PGPR) eliminate the effect of drought stress by altering the root morphology, regulating the stress responsive genes, production of phytohormones, osmolytes, siderophores, volatile organic compounds, exopolysaccharides and improving the 1-aminocyclopropane-1carboxylate (ACC) deaminase activities. The use of PGPR is an alternative approach to traditional breeding and biotechnology for enhancing the crop productivity. Hence the identification and characterization of microorganisms that promote the drought tolerance in important agriculture crops could be used to minimize the crop loss caused by limited water conditions. This review deal with recent progress about the rhizobacteria that have been identified to eliminate the harmful effect of drought stress in traditional agriculture crops.